PENGARUH KONSENTRASI TEPUNG PEPAYA DAN LAMA PENYIMPANAN TERHADAP SIFAT FISIK BEADS DAN VIABILITAS Lactobacillus acidophilus FNCC 0051 TERIMOBIL - Purba, Grace Sri; Widyastuti, Theresia Endang Widoeri; Kuswardhani, Indah (Jurnal Teknologi Pangan dan Gizi, 2016)
The purpose of this study was to determine the effect of papaya powder concentration and storage time to the physical properties of beads and viability of immobilized Lactobacillus acidophilus FNCC 0051. The Randomized Block Design (RBD) factorial design to be used. There were two (2) factors: concentration of papaya powder consisting of two (2) levels, which were 3% (w/v) and 6% (w/v) and storage time consisting of five (5) levels, which were 0, 7, 14, 21, and 28 days. Each treatment combinations repeated three (3) times. Testing is conducted on the beads’ diameter, beads’ texture (hardness, cohesiveness, springiness) and also immobilized cell’s viability. Data analyzed by ANOVA test (Analysis of Varians) at α = 5% and continued with DMRT (Duncan's Multiple Range Test) at α = 5 if the level of treatment had a significant effect. Beads diameter ranged 5.07 – 5.68 mm and the higher papaya powder concentration or the longer storage time would make the beads’s diameter bigger. Hardness ranged 29.2376 – 48.5756 g, cohesiveness ranged 0.3800 – 0.5211, and springiness ranged 0.8398 – 0.9889. The higher level concentration of papaya powder decrease beads’ hardness and cohesiveness but there’s no effect on springiness. The viability of immobilized Lactobacillus acidophillus FNCC 0051 ranged 8.6021 – 11.5474 log cfu/gram. Storage time significantly influenced the viability of immobilized cells, which the highest viable cells (11.1795 log cfu/g) obtained from 21 days of storage time.